Methoxy-Poly(ethylene glycol) Modified Poly(l-lactide) Enhanced Cell Affinity of Human Bone Marrow Stromal Cells by the Upregulation of 1-Cadherin and Delta-2-catenin. (14th April 2014) - Mao, Xueli; Chen, Zetao; Ling, Junqi; Quan, Jingjing; Peng, Hui; Xiao, Yin
Abstract : Poly(l -lactide) (PLLA), a versatile biodegradable polymer, is one of the most commonly-used materials for tissue engineering applications. To improve cell affinity for PLLA, poly(ethylene glycol) (PEG) was used to develop diblock copolymers. Human bone marrow stromal cells (hBMSCs) were cultured on MPEG- b -PLLA copolymer films to determine the effects of modification on the attachment and proliferation of hBMSC. The mRNA expression of 84 human extracellular matrix (ECM) and adhesion molecules was analyzed using RT-qPCR to understand the underlying mechanisms. It was found that MPEG- b -PLLA copolymer films significantly improved cell adhesion, extension, and proliferation. This was found to be related to the significant upregulation of two adhesion genes, CDH1 and CTNND2, which encode 1-cadherin and delta-2-catenin, respectively, two key components for the cadherin-catenin complex. In summary, MPEG- b -PLLA copolymer surfaces improved initial cell adhesion by stimulation of adhesion molecule gene expression.